TECHNOLOGY FOR THE DEVELOPMENT OF PROFESSIONAL SKILLS OF FUTURE TEACHERS OF THE RUSSIAN LANGUAGE BASED ON INNOVATIVE APPROACHES - Makhmadieva Rano Said-Abdullaevna (European Science Publishing, 2023)
The article deals with the basic concept of innovative approach to professional and methodological training of a future foreign language teacher of a new formation. The authors of the scientific work highlight the formation of methodical activism as the main goal of the innovative approach. The article also considers pedagogical conditions and means of formation of methodical credo of a new formation foreign language teacher: development of methodical thinking of a future teacher; development of ability of a teacher to adequately assess a specific pedagogical situation; development of ability to make professional methodical decisions; development of personal qualities of a new formation teacher: sociability, charisma, empathy, emotionality. The formation of the individual methodological credo of a creative teacher is provided by the integration of competence and reflexive approaches to the implementation of the course of linguodidactics in the universities of the pedagogical profile.
Keywords: travel journalism, travelogue, myth, tourist, guide, social neetworks, travel blogs, journey